Farmers Participation in Irrigation Management and Its Influence on Production and Productivity of Rice Farming - A. Nixia Tenriawaru; Muh. Hatta Jamil (International Journal of Agriculture System, 2014)
Utilization and management of irrigation, especially in the tertiary is the duty and responsibility of farmers involved and cooperate in farmer water user associations (P3A). This is confirmed in Article 1 No. PPRI. 20 of 2006 that, the utilization and management of tertiary irrigation network would be the part of farmers and requires an organization known as farmers’ water user associations (P3A). Through such participation, farmer members of P3A may gain knowledge derived from the results of their interactions with fellow members of P3A or other parties related to irrigation activities and ultimately may affect the achievement of the production and productivity of rice farming optimal. This study intends to examine the extent to which members of P3A farmer participation in irrigation management affect the production and productivity of rice farming in each tertiary, Bila Kalola irrigation. Survey method in this study is intended to obtain the required data through questionnaires to 324 farmer members of P3A in 41 affiliated P3A, which influence the participation of farmers on production and productivity of rice farming are analyzed through simple regression analysis and analysis of Cobb-Douglas production function. The results showed that: the more active participation of farmers in irrigation management activities, the increasing of production and productivity achieved, although this hypothesis has not been fully proven in each tertiary on Bila Kalola irrigation.